2023
DOI: 10.3390/antibiotics12020330
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Routine Laboratory Tests for Follow up of Patients Receiving Outpatient Parenteral Antimicrobial Therapy Run by Infectious Diseases Fellows

Abstract: Background: The infectious disease society of America (IDSA) recommends routine laboratory tests for all patients receiving outpatient parenteral antimicrobial therapy (OPAT) to monitor for adverse events. There are no data to support how often patients should take monitoring laboratory tests. In addition, the relevance of different laboratory tests commonly used for OPAT follow up is not clearly known. Methods: We conducted a retrospective observational cohort study over a 7-year study interval (1 January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Our results confirm previous studies regarding time to abnormal lab–associated OPAT-AEs [ 8 , 10 , 11 ]. Lam et al reported changing their institutional laboratory monitoring policy for patients receiving nonvancomycin OPAT to 1 set of labs at week 3 of therapy because they found that this corresponded to the highest-risk period for delayed-onset hypersensitivity reactions [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm previous studies regarding time to abnormal lab–associated OPAT-AEs [ 8 , 10 , 11 ]. Lam et al reported changing their institutional laboratory monitoring policy for patients receiving nonvancomycin OPAT to 1 set of labs at week 3 of therapy because they found that this corresponded to the highest-risk period for delayed-onset hypersensitivity reactions [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, this study specifically assessed neutropenia and not other potential abnormal lab–associated OPAT-AEs. Additionally, Frisby et al confirmed that an OPAT duration of 2–4 weeks was associated with lower risk of OPAT-related complications [ 10 ]. However, they included antimicrobials with known higher incidence of AEs in comparison with beta-lactams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation